Koncepcja arche w projekcji mentalnej Polaków i Rosjan (na materiale słowników asocjacyjnych) - Rodziewicz, Barbara (Acta Polono-Ruthenica, 2019)
This article describes the linguistic-cultural and associative field of the universal concept of arché (fire and water) in the Polish and Russian languages and identifies its general and specific cognitive symptoms in a variety of conceptual spheres. The author performs an analysis of the Polish and Russian associative dictionary that forms the so-called core of language consciousness.